Meningkatkan Kemampuan Pengembalian Bola Hasil Smash dari Lawan Berbasis Model Project Based Learning pada Pembelajaran Mata Kuliah Tenis Lapangan - Muhammad Ali; Ahmad Atiq; Novi Yanti; Ardrianus Nandi Pratama (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study aims to improve the ability to return smashed balls from opponents based on project-based learning models in learning tennis courses. This study used a quantitative descriptive method with a sports class action research style. Based on the study's results, among the 40 students who took part in the first cycle of learning tennis, 26 students had a completeness percentage of 65%, and 14 students still needed to finish with a percentage of 35%. Then proceed to cycle II; the overall result is 100% complete. In conclusion, students' learning outcomes have increased, and they completed 100% of learning tennis courses. Keywords: Learning Model, Project Based Learning, Tennis Field